The impact of health care expenditure and infectious diseases on labour productivity performance in Africa: do institutions matter? - Hassan, A. M.; Mohamed Nor, Norashidah; Mohd Noor, Zaleha (Universiti Putra Malaysia Press, 2016)
This study was rooted from the findings that for many years infectious diseases remain the major cause of death around the globe especially in Africa. Economic theory also predicts among others that HIV/AIDS reduces labour supply and productivity, and the GDP of Africa declines by 2-4% annually. In addition, institution is one of the reasons for slower growth in Africa. The study, therefore, examined the impact of health care expenditure per capita and infectious diseases such as HIV/AIDS and tuberculosis (TB) on labour productivity performance in Africa using System GMM Estimation methods for 50 panels of African countries from 2002-2011. The results show that health-care expenditure per capita is positive but insignificant to labour productivity performance in the region. The results also confirm the negative impact of infectious diseases on labour productivity performance in the region. Government effectiveness and control of corruption are positive and significant to the improvement of health care expenditure in Africa. In addition, the study also revealed that political instability and conflict also contribute positively to the spread of infectious diseases in the region. Thus, it is recommended that African governments and health-related development partners increase the financial amount allocated to the health sector. At the same time, more efforts are needed to curb and control the spread of infectious diseases through strengthened institutions to improve health-care expenditure in the region.